Mitochondrial and redox-based therapeutic strategies in Huntington's disease - Fão, Lígia (2020)
Significance: The molecular processes that determine Huntington's disease (HD) pathogenesis are not yet fully understood, and until now no effective neuroprotective therapeutic strategies have been developed. Mitochondria are one of most important organelles required for neuronal homeostasis, by providing metabolic pathways relevant for energy production, regulating calcium homeostasis, or controlling free radical generation and cell death. Because augmented reactive oxygen species (ROS) accompanied by mitochondrial dysfunction are relevant early HD mechanisms, targeting these cellular mechanisms may constitute relevant therapeutic approaches. Recent Advances: Previous findings point toward a close relationship between mitochondrial dysfunction and redox changes in HD. Mutant huntingtin (mHTT) can directly interact with mitochondrial proteins, as translocase of the inner membrane 23 (TIM23), disrupting mitochondrial proteostasis and favoring ROS production and HD progression. Furthermore, abnormal brain and muscle redox signaling contributes to altered proteostasis and motor impairment in HD, which can be improved with the mitochondria-targeted antioxidant mitoquinone or resveratrol, an SIRT1 activator that ameliorates mitochondrial biogenesis and function. Critical Issues: Various antioxidants and metabolic enhancers have been studied in HD; however, the real outcome of these molecules is still debatable. New compounds have proven to ameliorate mitochondrial and redox-based signaling pathways in early stages of HD, potentially precluding selective neurodegeneration. Future Directions: Unraveling the molecular etiology of deregulated mitochondrial function and dynamics, and oxidative stress opens new prospects for HD therapeutics. In this review, we explore the role of redox unbalance and mitochondrial dysfunction in HD progression, and further describe advances on clinical trials in HD based on mitochondrial and redox-based therapeutic strategies.